Battle Mountain - Box, C. J. (New York : G.P. Putnam's Sons, 2025)
After Axel Soledad and Dallas Cates devastate Nate Romanowski and Joe Pickett, Nate retreats to prepare for vengeance. Joe, asked by the governor to find a missing son-in-law in the Sierra Madre, teams up with rookie game warden Susan Kany. Their paths ultimately converge at Battle Mountain.
Keywords: Pickett, Joe -- (Fictitious character) -- Fiction; Crime -- Fiction; Falcons -- Fiction; Missing persons -- Fiction; Revenge -- Fiction; Sierra Madre (Wyo. and Colo.) -- Fiction; Detective and mystery fiction; Thrillers (fiction).